POGIL model on mathematical connection ability viewed from self-regulated learning - Enyta Ramadisae Putri; Budiyono Budiyono; Diari Indriati (International Journal of Evaluation and Research in Education (IJERE), 2020)
One area of education which has not escaped efforts to improve the Indonesian government is mathematics education. The Indonesian government must make good use of mathematics learning so that students can use the mathematical mindset to offset the pace of global competition. This research is an experimental research on the Process-Oriented Guided Inquiry Learning (POGIL) model on the ability of mathematical connections in terms of self-regulated learning. The design used in this study was a 2 × 3 factorial. The research sample was 179 students from 7th grade in three State Junior High Schools in Sukoharjo Regency, Central Java, Indonesia. The research sample consisted of an experimental group that subjected to the POGIL model and a control group that subjected to a direct learning model. This research instrument used was a written test and questionnaire. The data analysis technique used was a two-way ANOVA test with unbalanced cells and post hoc test. The results showed that: 1) the POGIL model produces better mathematical connection ability than the direct learning model, 2) Students with high category self-regulated learning have better mathematical connection ability than medium and low categories, and students with self-regulated learning the medium category have better mathematical connection ability than the low category.